(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Surgical treatment of dacryocystitis dates back to nearly 2000 years ago described as creating an artificial passageway into the nose using hot cautery to puncture through the lacrimal bone. Better understanding of lacrimal physiology and nasal and lacrimal anatomy through the centuries led to development of a procedure that would resemble a modern external DCR surgery in the 18th century. Intranasal approach operations had also been described in the 20th century. Advancements in methods of DCR surgery have been procured in view of cosmesis, amount of bleeding, duration of surgery, and outcome of the procedure. Aim/Objective: The aim of this study is to compare endonasal DCR and external DCR in the following prospects: I) Bleeding Time II) Sac Patency III) Surgical Time IV) Cosmesis Methods: This was a hospital based, interventional, prospective, non-randomized study of a total of 100 randomly selected patients of chronic dacryocystitis from OPD. 50 patients underwent external DCR and 50 patients underwent endonasal DCR. Young patients with good nasal space and without any nasal abnormality were operated for endonasal DCR, and old patients or those with nasal abnormalities were operated for external DCR. Preoperative assessment included an ENT evaluation, blood pressure, sac syringing, and blood investigations. Surgery was performed and post-operative assessments were conducted in the aspects of complications of surgery, intraoperative bleeding, surgical time and outcome of surgery. Results: From a total of 100 patients, 59% were females of which 54% were operated by endonasal DCR, with 30% of the population of total persons operated aging 60-70 years. There is more prevalence of dacryocystitis in females and in old aged patients in this study due to more chances of lacrimal pump failure in old age, and hormonal factors, smaller skull size and application on local cosmesis for females. Punctum patency after 6 months comparing endonasal and external DCR surgery using chi square formula proved a P value of 0.0008 which is highly significant showing that external DCR has significantly higher success rate than endonasal DCR. In the aspect of complications, the study proved a greater chance of recurrence of epiphora in external DCR, also the presence of a skin scar and wound dehiscence persists as a complication in external DCR due to the external skin incision which is not made in endonasal DCR. Conclusion: DCR is the treatment of choice for nasolacrimal duct obstruction, and it can be performed by external or endoscopic approach. Both approaches have minimal complications and comparable surgical outcome, hence the choice of surgery should depend upon the patient’s preference, availability of resources and surgeon’s expertise.